Biomechanics of anatomic and reverse shoulder arthroplasty. Issue 10 (19th October 2021) - Goetti, Patrick; Denard, Patrick J.; Collin, Philippe; Ibrahim, Mohamed; Mazzolari, Adrien; Lädermann, Alexandre
Abstract : The biomechanics of the shoulder relies on careful balancing between stability and mobility. A thorough understanding of normal and degenerative shoulder anatomy is necessary, as the goal of anatomic total shoulder arthroplasty is to reproduce premorbid shoulder kinematics. With reported joint reaction forces up to 2.4 times bodyweight, failure to restore anatomy and therefore provide a stable fulcrum will result in early implant failure secondary to glenoid loosening. The high variability of proximal humeral anatomy can be addressed with modular stems or stemless humeral components. The development of three-dimensional planning has led to a better understanding of the complex nature of glenoid bone deformity in eccentric osteoarthritis. The treatment of cuff tear arthropathy patients was revolutionized by the arrival of Grammont's reverse shoulder arthroplasty. The initial design medialized the centre of rotation and distalized the humerus, allowing up to a 42% increase in the deltoid moment arm. More modern reverse designs have maintained the element of restored stability but sought a more anatomic postoperative position to minimize complications and maximize rotational range of motion. Cite this article: EFORT Open Rev 2021;6:918-931. DOI: 10.1302/2058-5241.6.210014